PENGARUH KUALITAS LAYANAN MANAJEMEN TERHADAP PRESTASI BELAJAR MELALUI KEPUASAN MAHASISWA DI INSTITUT ISLAM MAMBA’UL ‘ULUM SURAKARTA - Fathurrahman, Muhammad; Aryati, Ida; Mursito, Bambang (MAMBA'UL 'ULUM, 2024)
The purpose of the study was to examine the indirect effect of management service quality on learning achievement through student satisfaction. Management services include lecturer performance, academic services and infrastructure facilities. Testing the direct effect of management services on student achievement and on student satisfaction. Research data were taken from the population of active students of IIM Surakarta. The sample used was 342 students with Purposive sampling technique based on active students with a minimum GPA of 3.5. Data collection using questionnaires with structural equation model (SEM) analysis techniques. The results of the study based on the Direct Effect (path coefficient) table of direct hypothesis influence, show that lecturer performance and infrastructure have a positive and significant effect on student achievement and academic services have no significant effect on student achievement, management services have a positive and significant effect on student satisfaction. The result of the indirect hypothesis influence is that student satisfaction plays a role in mediating the effect of management services on student achievement. Where, H1, H2, H4, H5, H6, H7, H8, H9 and H10 are accepted and H3 is rejected.